Association between maternity waiting home stay and obstetric outcomes in Yetebon, Ethiopia: a mixed-methods observational cohort study - Erickson, Anne K.; Abdalla, Safa; Serenska, Alice; Demeke, Bete; Darmstadt, Gary L. (BMC pregnancy and childbirth, 2021)
Background A strategy for reducing adverse pregnancy outcomes is the expanded implementation of maternity waiting homes (MWHs). We assessed factors influencing MWH use, as well as the association between MWH stay and obstetric outcomes in a hospital in rural Ethiopia. Methods Data from medical records of the Glenn C. Olson Memorial Primary Hospital obstetric ward were cross matched with records from the affiliated MWH between 1 and 2011 to 31 March 2014. Poisson regression with robust variance was conducted to estimate the relative risk (RR) of childbirth complications associated with MWH use vs. non-use. Five key informant interviews of a convenience sample of three MWH staff and two users were conducted and a thematic analysis performed of social, cultural, and economic factors underlying MWH use. Results During the study period, 489 women gave birth at the hospital, 93 of whom were MWH users. Common reasons for using the MWH were post-term status, previous caesarean section/myomectomy, malposition/malpresentation, and low-lying placenta, placenta previa, or antepartum hemorrhage, and hypertension or preeclampsia. MWH users were more likely than non-users to have had a previous caesarean Sec. (15.1 % vs. 5.3 %, p < 0.001) and to be post-term (21.5 % vs. 3.8 %, p < 0.001). MWH users were also more likely to undergo a caesarean Sec. (51.0 % vs. 35.4 %, p < 0.05) and less likely ( p < 0.05) to have a spontaneous vaginal delivery (49.0 % vs. 63.6 %), obstructed labor (6.5 % vs. 14.4 %) or stillbirth (1.1 % vs. 8.6 %). MWH use ( N = 93) was associated with a 77 % (adjusted RR = 0.23, 95 % Confidence Interval (CI) 0.12–0.46, p < 0.001) lower risk of childbirth complications, a 94 % (adjusted RR = 0.06, 95 % CI 0.01–0.43, p = 0.005) lower risk of fetal and newborn complications, and a 73 % (adjusted RR = 0.27, 95 % CI 0.13–0.56, p < 0.001) lower risk of maternal complications compared to MWH non-users ( N = 396). Birth weight [median 3.5 kg (interquartile range 3.0-3.8) vs. 3.2 kg (2.8–3.5), p < 0.001] and 5-min Apgar scores (adjusted difference = 0.25, 95 % CI 0.06–0.44, p < 0.001) were also higher in offspring of MWH users. Opportunity costs due to missed work and need to arrange for care of children at home, long travel times, and lack of entertainment were suggested as key barriers to MWH utilization. Conclusions This observational, non-randomized study suggests that MWH usage was associated with significantly improved childbirth outcomes. Increasing facility quality, expanding services, and providing educational opportunities should be considered to increase MWH use.